PENGARUH PROMOSI DAN ATRIBUT PRODUK TERHADAP KEPUTUSAN NASABAH DALAM MEMILIH TABUNGAN EKASAVE PADA BANK EKA KANTOR PUSAT METRO - Karnila Ali (Universitas Muhammadiyah Metro Lampung, 2017)
Customers’ decision to save their money is a final effect of a purchase, which is defined as an attitude and an intention to behave in the future and expressed through things such as, a commitment to buy a product from a company if they need other products, a commitment to provide recommendations to others, intention to increase the amount of savings, intention or desire to give positive things to the company. In the decision making process of customers in choosing Ekasave saving product, it is affected by several variables, namely promotions and product attribute.This study aims to analyze the effects of promotion and product attribute on customer decision in choosing Ekasave saving at Bank Eka of Metro Head Office. The research method used in this study was quantitative. The research samples were Ekasave saving customer data in 2015, Bank Eka, Metro Head Office.The analytical method used was F test (simultaneous), T test (partial), determination coefficient analysis (R2), and multiple linear regression analysis. Based on the research results, Multiple Linear Regression Analysis for promotion variable had positive value with t count by 8.226 and product attribute had positive value with t count by 4.631. Therefore, promotion and product attribute simultaneously provide positive effects on customer decision with F count by 54.275.Keywords: Promotion, Product Attribute, and Customer Decision